2020
DOI: 10.1063/1.5145298
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Hall current and radiation on MHD micropolar non-Newtonian hybrid nanofluid flow between two surfaces

Abstract: In this article, the magnetohydrodynamic flow and heat transmission of a micropolar hybrid nanofluid between two surfaces inside a rotating system are examined. The Hall current and thermal radiations are also considered for the flow system. In this article, a base fluid is taken as water, while graphene oxide (GO) and copper (Cu) are applied as hybrid nanoparticles. The flow is assumed to be in a steady state. The governing partial differential equations along with boundary conditions for the modeled problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The thickness of the thermal boundary layer reduces when the Prandtl number increases. 6. The symmetrical nature of branches exists for the solution of the angular velocity.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of the thermal boundary layer reduces when the Prandtl number increases. 6. The symmetrical nature of branches exists for the solution of the angular velocity.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Hayat et al [3] analytically studied the radiative MHD flow of viscoelastic nanofluid and found that radiation helps to improve the thermal conductivity and temperature of the fluid. Articles of the implementations, formulation, and thermomechanical characteristics of hybrid nanofluids were already undertaken by the following researchers: Subhani et al [4], Qi et al [5] and Islam et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the y-axis has been set perpendicular to the plate's walls. Under these suppositions, the Navier–Stokes equations are composed as in 11 , 47 , and 48 .
Figure 1 The geometry of the problem.
…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Shah et al 7 deliberated thermal augmented EMHD micropolar hybrid nanofluid flow on a horizontal surface. Islam et al 8 surveyed the thermal flow for micropolar hybrid nanofluid (GO + Cu + H 2 O) flow amid two plates. The efficiency of hybrid nanofluid has been analyzed by Khashi’ie et al 9 with nanoparticles of copper and alumina in a base fluid taken as water.…”
Section: Introductionmentioning
confidence: 99%